DR 시스템에서 모드 변화에 따른 구리필터의 유용성 평가 - 김재겸(Kim Jae-Kyeom), 김정구(Kim Jeong-Koo) (방사선기술과학, 2021)
This study confirmed the usefulness of the copper filter according to the mode change by comparing and analyzing the energy change according to the application of the copper filter and the change in effective dose and image quality according to the distance to the subject in the DR(Digital Radiography) system. The average energy increased when the copper filter was applied and the reduction rate by 50% of mAs was increased as the thickness of the copper filter increased according to the application of the 10 kVp rule in AEC mode. The effective dose decreased as the thickness increased when the copper filter was applied in AEC(Automatic Exposure Control) mode and manual mode according to the application of the 10 kVp rule, and the decrease rate decreased with increasing 10 kVp increments. As a result of analyzing the dicom images for AEC mode and manual mode with Image J. the PSNR(Peak Signal to Noise Ratio) values were approximate values of less than 30 dB for each mode and for each copper filter thickness. When the copper filter was applied, the average energy increased, so when the 10 kVp rule was applied, the mAs for each mode could be reduced, and the effective dose could also be reduced. However, as the distance and tube voltage increased, the reduction rate of mAs decreased, and the quality of the image was found to decrease when the copper filter was applied, but there was no difference in quality of the image when the copper filter thickness increased.